KEPERCAYAAN DAN PENGALAMAN MEREK TERHADAP KECINTAAN MEREK DALAM INDUSTRI OTOMOTIF: EKUITAS MEREK SEBAGAI VARIABEL MEDIASI - Saputra, Allyya; Darka (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Abstrak This Research examines the relationships among brand trust, brand experience, brand equity, and brand love within Indonesia’s automotive industry, based on responses from 374 consumers across five regions of Jakarta. Grounded in the Customer-Based Brand Equity (CBBE) framework and emotional branding theory, the study analyzes both direct and mediating effects of brand trust and brand experience on brand love, with brand equity as the mediating variable. Employing a quantitative, causal, and cross-sectional design under a post-positivist paradigm, data were collected through a validated 4-point Likert scale questionnaire and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) via SmartPLS. The constructs measured include brand trust (credibility, transparency, consistency, reputation), brand experience (sensory, affective, cognitive, behavioral), brand equity (awareness, association, perceived quality), and brand love (attachment, identification, loyalty, advocacy). Findings reveal that brand trust and brand experience significantly and positively influence brand equity and brand love. Moreover, brand equity partially mediates these relationships, demonstrating its crucial role in translating trust and experiential perceptions into emotional attachment. The model showed strong reliability and validity (Cronbach’s α > 0.80, AVE > 0.50, CR > 0.85)..